Contemporary occupational therapy philosophy and practice in hospital settings. (3rd April 2021) - Murray, Alice; Di Tommaso, Amelia; Molineux, Matthew; Young, Anna; Power, Penny
Abstract: Background: Occupational therapists have sought to reconnect with the foundations of the profession for many years, and a key focus has been the place of occupation in practice. Existing literature suggests that therapists working in acute settings experience difficulties practicing in ways that centralise occupation. Aim/Objective: This scoping review aimed to explore the existing literature on contemporary occupational therapy philosophy and practice in acute hospital settings. Methods: A five step scoping review process was implemented. Four electronic databases were searched using a combination of search terms. Searching reference lists of papers was also completed. Results were summarised using numeric and thematic analysis. Results: Twenty four publications were included. Four themes were identified; attitudes towards occupation-based practice, benefits of occupation-based approaches, challenges implementing occupation-based practice, and strategies to overcome challenges. Conclusion and Significance: Findings highlighted therapists value occupation as an important aspect of practice, however they experience many environmental and personal challenges in acute settings. Strategies to overcome these challenges related to individual's changing their practice to be more occupation-focussed and changes within the practice context including adapting environments, documentation and intervention protocols to focus on occupation. These strategies may support therapists to align practice with their professional values.